Características de idosas participantes de um programa com atividades multidisciplinares - ABREU, Leudyenne Pacheco de (2023)
Objective: Identify the characteristics of elderly women participants in a program with multidisciplinary activities and the risk of sarcopenia. Materials and methods: This is a cross-sectional, descriptive study, carried out with women between 60 and 84 years old, members of a program with multidisciplinary activities for the elderly at the Federal University of Maranhão. Questionnaires were used to collect sociodemographic data, sarcopenia screening, physical activity level, and depressive symptomatology. For muscle strength, handgrip strength (HGS) and the sit-to-stand test (STST) were used. For the muscle mass index (MMI), tetrapolar electrical bioimpedance was used, and for physical performance, the walking speed test (WS), the Timed-up-and-go test (TUG), and the Short Physical Performance Battery (SPPB) were used. In addition, anthropometric measurements of height and body weight, and calf circumference were performed. The cut-off adopted were those stipulated by the 2nd European Working Group on Sarcopenia in Older People (EWGSOP2). The Shapiro-Wilk test was used for normality of the data and Spearman's test for correlation of the variables. Data were presented as mean±standard deviation, as well as frequency and percentage and p≤0.05. Results: Fifty elderly women participated in the study with mean age values of 67.12±5.12 years, height 1.54±0.05m, body mass 62.46±10.44kg. When screened for sarcopenia with the SARC-F questionnaire, no signs suggestive of the disease were observed. When evaluating the diagnostic criteria, it was observed that 16% of the elderly women had probable sarcopenia (HGS<16kg; STST>15seconds), and no diagnosis of sarcopenia or severe sarcopenia was observed. In the risk factor analysis, the presence of malnutrition (12%), low calf circumference (6%), physical inactivity (34%), high sedentary behavior (82%), mild depressive symptomatology (10%), and the presence of comorbidities (96%) were observed. When investigated for possible correlation between risk factors and sarcopenia criteria, there was a correlation between body mass index (BMI) and MMI (rho=0.37, p=0.008) and TUG (rho=0.288, p=0.043). Calf circumference also correlated with HGS (rho=0.434; p=0.002) and MMI (rho=0.300; p=0.035), and correction was observed with BMI (rho=0.544; p<0.001) and body fat percentage (rho= 0.431; p=0.002). Among the diagnostic criteria, correlation was observed between HGS and MMI (rho=0.407; p=0.003). Correlations were observed between STST with TUG (rho=0.382; p=0.006), WS (rho= 0.474; p=0.003) and SPPB (rho= 0.887; p<0.001), in addition to the correlation between WS and SPPB (rho=0.370; p=0.008) and TUG (rho= 0.457; p<0.001). Conclusions: Community-dwelling elderly women participating in a multidisciplinary program are characterized by a low risk of sarcopenia, since most have strength levels above reference values. Despite this population presenting satisfactory values for calf circumference, level of physical activity, body mass index, and reduced rate of depressive symptoms, they have as remarkable characteristics a high percentage of body fat, high sedentary behavior, and a high number of comorbidities.